Survey of Physical Functioning and Prevalence of Chronic Illnesses Among the Elderly People - Aghil Habibi; Mohammad Taghi Savadpoor; Behnam Molaei; Mahmod Samshiri; Mostafa Ghorbani (University of Social Welfare & Rehabilitation Sciences, 2009)
Objectives: The purpose of this study was to determine the OF physical functioning level and prevalence of chronic illness among elderlypeople in west region of Tehran. Methods & Materials: This study was a descriptive and cross-sectional study. A multi-stage sampling was used and 410 community residents who were over 60 years old were selected from west region of Tehran.Descriptive statistics, T-test and ANOVA were used to analysis data. Results: There were significant relations between ADLs and ‘Gender’, ‘Economic status’, ‘Health status’, ‘Education’ and ‘Number of chronic illness’ (P<0.05). Furthermore there were significant relations betweenthe IADLs and ‘Age’, ‘Gender’, ‘Economic status’, ‘Living arrangement’, ‘Health status’, ‘Education’ and ‘Number of chronic illness’ (P<0.05). Also the result of the study showed that 86.8% of participants had at least one chronic illness. Conclusion: This study showed that different factors affect physical functioning of elderly people. Also they were totally independent from a status of physical functioning (ADL & IADL) and the majority of them had at least one chronic illness. Health care professionals should enhance the physical functioning in elderly people by facilitating their life through educational programs and regular physical check-ups whichwill maintain and increase a healthy and active life.